Pengaruh Corporate Governance dan Kualitas Audit Terhadap Integritas Laporan Keuangan Pada BUMN 2021-2024 - Gracia Juliana Sumadi; Febryanti Simon (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The integrity of financial statements is a fundamental element in maintaining stakeholder trust in a company’s financial information. However, the phenomenon of financial statements that do not reflect actual information still frequently occurs, including within state-owned enterprises (SOEs) and their subsidiaries. This condition indicates that maintaining the integrity of financial statements remains a challenge requiring greater attention, as many companies still neglect the principle of prudence in financial reporting. The purpose of this study was to determine empirically the influence of independent commissioner, audit committee, and audit quality on the integrity of financial statements in state-owned enterprises (SOEs) and their subsidiaries that listed on Indonesia Stock Exchange (IDX) for the 2021-2024 period. This study used a quantitative method using purposive sampling with a sample of 18 companies that met the criteria. Data analysis was conducted using multiple linear with IBM SPSS 26.0. The result shows that audit quality has a positive significant effect on the integrity of financial statements. Meanwhile, independent commissioners and audit committees have no significant effect on the integrity of financial statements. These findings suggest that supervisory function is not yet optimal in ensuring that financial information is presented transparently and reflect the company’s actual condition.